Divorce Case Rate in Young Families During the Covid-19 Pandemic in 2021 (Case Study of the Religious Court of Binjai City) - Adrian, Dika; Lubis, Fauziah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to examine more deeply the level of divorce cases in young families during the COVID-19 pandemic in 2021 at the Binjai City Religious Court. Specifically, this research aims to answer two problem formulations: (1) the percentage rate of divorce in young families during the pandemic; and (2) the factors that influence the increase in divorce. This research includes qualitative research using a case approach. This type of empirical research uses primary data, namely data from the Religious Court of Binjai City regarding contested divorce in young families and data from the Supreme Court Decision Repository. Secondary data in the form of interviews with Binjai religious court employees, books, journals, and literature regulations related to this research. From this study, the researchers found that divorce cases in young families in 2021 increased compared to the years before the pandemic. The results showed an increase in the percentage of divorce in young families by 15%, namely 408 cases in 2021 compared to 2020, which was only 347 cases. The main factors are economic and psychological pressures due to the pandemic.